The Learners’ Characteristics towards Achieving Learning Performance in Blended Learning - Mustafa bin Izahar, Mohd; Zubeidah Zachariah, Tirza; Nair d/o Subagaran, Asha; d/o Elangkeswaran, Dhurgeswari (KnE Social Sciences, 2022)
Blended learning is a combination of traditional face-to-face classroom situation and online situation. In this paper, the study focuses on the characters of UNISEL students towards achieving learning performances in blended learning. A questionnaire is directed to 103 respondents to answer. There are 3 sections in the questionnaire related to blended learning. Each section is followed by 5 questions. Hence, it shows that different students’ have different opinions towards blended learning despite their age, gender, course and faculty. This finding shows that some students prefer to use blended learning. However, there are some who think that blended learning is not suitable for them. Learners’ characteristics and interaction towards learning performance is the major outcome of this research. In conclusion, learners characteristics towards achieving the learning performance in blended learning is crucial in order to find a solution and the remaining problem that has not been figured out is a focus point for the future researchers. Keywords: blended learning, learners’ characteristics, learning performance